Prevention of Bias and Discrimination in Clinical Practice Algorithms - Shachar, Carmel; Gerke, Sara (JAMA : the journal of the American Medical Association, 2023)
This Viewpoint discusses a proposed DHHS rule to address discrimination in clinical algorithms and the need for additional considerations to ensure the burden of liability for biased algorithms is not disproportionately placed on health care professionals.